Correlation Between sCD28 and sCD80 Levels with Disease Actiity of SystemicLupus Erythematosus (SLE) Patients Based on SLEDAI Score - Ahmad Harissul Ibad (Indonesian Journal of Rheumatology, 2024)
Background: Systemic Lupus Erythematosus (SLE) is an autoimmune diseasewith multisystem involvement that is caused by multifactorial. Prolongedexposure to autoantigens and sustained immune system activation, particularlyin memory T lymphocytes, can contribute to premature immunosenescence.Soluble costimulatory molecules such as sCTLA-4 and sCD86, originating fromCTLA-4 and CD86 respectively, contribute to the progression ofimmunosenescence in patients with SLE. This condition is associated with highermorbidity and mortality. This study aimed to investigate the relationshipbetween elevated levels of sCTLA-4 and sCD86 and the severity of SLE diseaseactivity, as assessed by the SLEDAI score. Methods: The study employed ananalytical observational design with a cross-sectional approach, involving 35female participants diagnosed with SLE according to the 2012 SLICC criteria. SLEdisease activity was assessed using the SLEDAI score, and serum levels of sCD28and sCD80 were measured using the ELISA method. The Mann-Whitney test wasused for group comparisons, while the Spearman test was conducted forcorrelation analysis, with statistical significance defined as p < 0.05. Results: SLEpatients had an average sCD28 and sCD80 level of 24.93 and 27.41, respectively.Spearman test results showed that sCD28 level had a significant correlation withSLEDAI score [R=0.364; p=0.031 (p<0.05)], while sCD80 level did not correlatesignificantly with SLEDAI score [R=0.048; p=0.786 (p<0.05)]. Conclusion: Therise in sCD28 levels showed a positively correlation with the SLE severity activity,as indicated by the SLEDAI score.